Morphometric sex determination from mastoid triangle in South Indian population - Singh, Pankaj Kumar; Menezes, RG; Shetty, BSK; Rastogi, P; Kanchan, T; Rao, J; P, P; Y.P, RB (Health Renaissance, 2017)
No abstract available Health Renaissance 2015;13(2): 105-113